Cover crop-specific root-derived biopore structure is associated with biopore sheath bacterial facets in compacted soil columns - Peng Xiong; Guilong Li; Zejun Luo; Hao Li; Zhengfu Yue; Yueming Chen; Xiaolin He; Xiong Fang; Jia Liu; Jingjing Peng (Soil and Tillage Research, 2026)

Astaxanthin activates PI3K/AKT and AMPK signaling to alleviate oxidative stress and improve mouse oocyte In vitro maturation - Mei Zhou; Mengzhen Luo; Yueming Yuan; Liqin Han; Lin Chen; Shangquan Gan (Theriogenology, 2026)

Characterization of flavor compounds and core functional microorganisms during pile fermentation of Liupao tea - Yanjun Chen; Yuelan Pang; Yueming Liang; Zhusheng Liu; Zhonghua Liu; Qiming Hu; Fujing Pan (Food Chemistry, 2026)

Decoupling natural ventilation and traffic noise in railway-adjacent dwellings: Field measurements and passive design strategies - Qi Zhao; Chen Chen; Meng Ouyang; Yitong Wang; Yueming Wen (Energy and Buildings, 2026)

Soybean integration increases pore connectivity and particulate organic matter while reducing shrinkage in saline Fluvo-aquic soil: An X-ray CT study - Tianyu Ding; Zichun Guo; Yueming Chen; Shenzhong Tian; Jianli Liu; Xinhua Peng (Soil and Tillage Research, 2026)

MaHPCA1 alleviates chilling injury in banana fruit - Yu Hou; Peipei Fan; Xiangbin Xu; Zhengke Zhang; Yonggui Pan; Lanhuan Meng; Lisha Zhu; Haiming Chen; Jianbo Xiao; Yueming Jiang; Jiali Yang (Postharvest Biology and Technology, 2026)

Differential effects of Cl- and SO42- anion systems on Ca2+-Mg2+-Mn2+ carbonate biomineralization induced by the halophilic Bacillus dokdonensis: Implications for Mn2+-containing saline wastewater treatment - Xueting Chen; Yueming Zhao; Hui Zhao; Memon Kashif Ali; Ran Shu; Bo Liu; Boyu Cai; Runxi Yin; Zuozhen Han; Huaxiao Yan (Journal of Hazardous Materials, 2026)

Musa acuminata calmodulin-binding transcription activator 4 enhances fruit quality maintenance of banana during cold storage - Ying Li; Youxia Shan; Wanqi Chen; Rufang Deng; Xuewu Duan; Taotao Li; Yueming Jiang (Food Chemistry, 2026)

Arachidonic acid enhances chilling tolerance in banana fruit via coordinated antioxidant system, energy homeostasis and phenylpropanoid metabolism - Youxia Shan; Ying Li; Taotao Li; Wanqi Chen; Xuewu Duan; Yueming Jiang (Food Chemistry, 2026)

Suppressing spectral broadening via intramolecular noncovalent interactions for high-efficiency solution-processed multi-resonance TADF OLEDs - Tao Zhou; Guimin Zhao; Yumiao He; Taiping Chen; Wenwen Tian; Yueming Sun; Wei Jiang (Chemical Engineering Journal, 2026)

Effects of volcanic altitudes on the rhizosphere microbial community composition and structure of Euphorbia maculata - Yaozhou Zhang; Han Lin; Qixiu Cheng; Haining Wang; Yiming Zhang; Yueming Bao; Rui Qin; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2026)

Torque teno virus in the lower respiratory tract: association with immunosuppression but not mortality in severe pneumonia—a multicenter retrospective cohort study - Xian Zhang; Lifei Chen; Fang Wang; Xiaofang Xu; Yueming Wu; JunLong Xu; Yongan Xu; Xuwei He (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Host-derived Bacillus velezensis enhances intestinal structure, antioxidant capacity, and pathogen resistance in the American bullfrog (Aquarana catesbeiana) - Yueming Hu; Han Lin; Mengzhen Jiang; Changyi Lin; Hua Li; Jingyang Sun; Kesong Chen; Yebing Yu; Chun Liu (Archives of Microbiology, 2026)

Waste eggshell-modified biochar for phosphorus recovery and its potential reuse as a sustainable fertilizer - Yixuan Feng; Yueming Chen; Xilin Guan; Zichao Zhao; Xinhao Gao; Xiaoning Liu; Shenzhong Tian (Journal of Environmental Chemical Engineering, 2026)

Catalase is a critical virulence factor in Aeromonas schubertii infection of snakehead fish (Channa argus) - Mengzhen Jiang; Haiyan Gong; Qing Wang; Han Lin; Yueming Hu; Hua Li; Jingyang Sun; Kesong Chen; Biao Jiang; Wei Li; Youlu Su; Chun Liu (Antonie van Leeuwenhoek, 2026)

Online monitoring of deposit-induced corrosion in a Waste-to-Energy boiler - Wenjie Liu; Yafang Wang; Yan Wang; Yongjun Liu; Anming Du; Qiongyu Ren; Xinran Zheng; Xiyu Chen; Minmin Zhou; Yueming Wang; Lunbo Duan (Waste Management, 2026)

Exploring relaxation features for rapid identification of olive oil adulteration via low-field nuclear magnetic resonance integrated with chemometrics - Yulong Chen; Xuewen Qin; Shan Zeng; Bing Li; Yueming Tao; Huanjun Hu (Food Research International, 2026)

In vitro digestion and faecal fermentation of starch-lipid complexes with distinct crystalline forms prepared by extrusion-cooking - Chen Chao; Rong Sun; Yueming Zhu; Cuiping Wang; Jinglin Yu; Shujun Wang (Carbohydrate Polymers, 2026)

Piperlongumine Inhibits Malignant Progression of Esophageal Squamous Cells Through the PI3K/AKT Signaling Pathway - Jun Wang; Yueming Chu; Guangbing Hu; Shiqi Liang; Yutong Cui; Ji Zuo; Zichen Luo; Xinrui Chen; Xiaobo Wang; Zhenghang Yu; Zhongyang Zhang; Xianfei Wang (Biochemical Genetics, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Single-cell dissection of pleural and systemic immunity uncovers pathogen-specific immune reprogramming in tuberculosis versus lung adenocarcinoma - Sifei Yu; Yueming Liang; Jing Chen; Beiying Zhang; Chuling Zhang; Yuwen Zhao; Rong Yan; Yichu Nie; Xiaofan Mao (Inflammation Research, 2026)

Integrating Traditional and Artificial Intelligence Methods in Dust Aerosol Research: A Comprehensive Review - Tong Sha; Rui Zheng; Yueming Cheng; Zhenan Yao; Qingcai Chen (Current Pollution Reports, 2026)

Pharmacological inhibition of USP7 attenuates deltamethrin-induced neuronal ferroptosis via GPX4 stabilization - Minjia Wu; Yang Chen; Peixuan Ma; Wen Pan; Yaqin Deng; Lexing Wei; Guodong Lu; Michael Aschner; Yueming Jiang; Jing Zhou; Xiaowei Huang (Toxicology and Applied Pharmacology, 2026)

Adenine regulates chilling injury via energy signaling salvage by purine permease MaPUP4 in banana fruit - Youxia Shan; Ying Li; Wanqi Chen; Junxian He; Xuewu Duan; Yueming Jiang (Postharvest Biology and Technology, 2026)

Non-linear interaction behavior of mixed industrial solid wastes in circulating fluidized beds: Reacting MP-PIC simulation - Minmin Zhou; Xiuzhi Wang; WenQiang Chen; Qiuchen Sun; DongFu Wang; Zhijiang Han; Chenxi Lu; Yueming Wang; Lunbo Duan; Wojciech P. Adamczyk (Fuel, 2026)

Drivers of soil carbon and nitrogen cycling during plantation succession: linking aboveground plant communities with belowground microbial networks - Xianghua Zuo; Wei Zhao; Jinying Li; Yunxiao He; Yueming Zhao; Ming Xing; Jiangnan Li; Xia Chen (Plant and Soil, 2026)

Bromide-containing surfactants enabling singlet oxygen-dominated non-radical oxidation process for efficient degradation of aromatic pollutants in soil and groundwater - Yueming Han; Zhuolun Li; Guanqing Chen; Hengxin Liu; Shichao Feng; Yuntao Guan; Lixun Zhang (Process Safety and Environmental Protection, 2026)

Apyrase MaAPY2 regulates the chilling tolerance of banana fruit as a negative modulator - Ying Li; Wanqi Chen; Shule Chen; Zhuojia Mao; Shihan Huang; Rufang Deng; Dandan Zhang; Taotao Li; Xuewu Duan; Yueming Jiang (Postharvest Biology and Technology, 2026)

Contrasting soil structure and yield responses to 8-year conservation tillage in Fluvo-aquic and Shajiang black soils - Tianyu Ding; Zichun Guo; Yueming Chen; Zizhou Yu; Shenzhong Tian; Jianli Liu; Xinhua Peng (European Journal of Agronomy, 2026)

Effect of phenolic hydrogen on the formation of chitosan -prenylated flavonoids nanocomplexes - Jinping Wang; Jiawen Chen; Yueming Jiang; Bao Yang; Lingrong Wen (Food Hydrocolloids, 2025)

Numerical modeling of multi-directional lateral behaviour of pile foundations for offshore wind turbines in clay - Shasha Ren; Deqiong Kong; Yueming Du; Yuan Chen; Bin Zhu (Ocean Engineering, 2025)

Pore structure modulation and surface functionalization boosted adsorption of PFAS on porous carbon: Experimental and theoretical investigations - Bei Zhang; Daiki Moriyama; Thilini Maheshika Herath; Huan Zhao; Yuqiao Bai; Yueming Dang; Wei Liu; Hiromichi Kato; Koichi Yamamoto; Yasuhide Mochizuki; Naoki Arimitsu; Akira Nakajima; et al. (Journal of Hazardous Materials, 2025)

Molecular mechanisms of superheated steam-induced modifications enhancing ovalbumin functional properties: Insights from site identification and peptidomic analysis - Haiqi Chen; Zuohua Xie; Feifei Wang; Zongcai Tu; Pingwei Wen; Siqiong Zhang; Hui Wang; Yueming Hu (Food Chemistry, 2025)

A new point mutation (E198T) in β2-tubulin confers resistance to carbendazim in Fusarium incarnatum - Zelong Peng; Zhili Yuan; Yueming Jin; Furong Chen; Zhiwen Wu; Yiping Hou (Pesticide Biochemistry and Physiology, 2025)

A novel mutation type S420I in Myosin-5 confers resistance to Phenamacril in Fusarium fujikuroi - Yueming Jin; Zelong Peng; Zhili Yuan; Furong Chen; Feng Hu; Hongzhou Chen; Yiping Hou (Pesticide Biochemistry and Physiology, 2025)

In vivo cell migratory behavior drives therapeutic efficacy evidenced by SWIR fluorescence imaging - Huizhu Li; Xiao Zhang; Shunyao Li; Yueming Wang; Shingo Ogura; Kemeng Shao; Xiner Du; Yan Wo; Shiyi Chen; Jun Chen; Xuanfeng Qin; Yunxia Li; et al. (Chemical Engineering Journal, 2025)

Homoeologous recombination-based transfer and cytological mapping of the novel powdery mildew resistance gene Pm7C from Aegilops caudata - Yueming Ren; Mengzhen Luo; Yajun Feng; Qifan Chen; Chao Ma; Wenxuan Liu; Fu Guo; Qianwen Liu; Muhammad Amjad; Ranran Jia; Xinpei He; Xiang Ji; et al. (Theoretical and Applied Genetics, 2025)

The interaction between mycorrhiza and phoD-harbouring bacteria influencing soil available phosphorus in Pinus massoniana plantations - Lifen Li; Yueming Liang; Qiang Li; Fujing Pan; Zhangqi Yang; Yanlan Wei; Yijing Li; Yanjun Chen; Hanlian Qin; Guangping Xu (Applied Soil Ecology, 2025)

Overcoming the Diagnostic Challenges in Cutaneous Cryptococcosis Caused by Cryptococcus neoformans: A Case Study Utilizing Metagenomic Next-Generation Sequencing - Liujun Lu; Yulin Chen; Minfang Leng; Shuquan He; Qunlan Liu; Songyun Zou; Yueming Liu; Feixiang Fan (Mycopathologia, 2025)

Frog virus 3: Prevalence survey and quantitative analysis in American bullfrogs using TaqMan MGB probe real-time fluorescence quantitative PCR - Hua Li; Xiaobing Liu; Jingyang Sun; Han Lin; Kesong Chen; Yueming Hu; Mengzhen Jiang; Biao Jiang; Wei Li; Youlu Su; Qing Wang; Chun Liu (Aquaculture, 2025)

Responses of microbial community to different depths in volcanic soils of Nvshan Volcano - Jin Chen; Haining Wang; Ye Cui; Yiming Dai; Yueming Bao; Rui Qin; Qixiu Cheng; Xiaoyu Li (World Journal of Microbiology and Biotechnology, 2025)

MEK1 inhibition ameliorates mitochondrial-dependent apoptosis induced by deltamethrin in mouse hippocampal neuron HT22 cells - Lexing Wei; Yang Chen; Minjia Wu; Peixuan Ma; Huan Wang; Yueming Jiang; Michael Aschner; Jing Zhou; Guodong Lu; Lina Zhao; Xiaowei Huang (Toxicology in Vitro, 2025)

The role of SYK phosphorylation in LPS-induced immunoglobulin responses of B cells in large yellow croaker (Larimichthys crocea) - Hongjun Xie; Shuangshuang Cao; Yueming Chen; Zhiqiang Wang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2025)

Effects of storage durations on flavour and bacterial communities in Liupao tea - Yueming Liang; Zhusheng Liu; Yuelan Pang; Min Li; Shengmeng Zheng; Fujing Pan; Chunyu Guo; Qianhua Wu; Ting Chen; Qiang Li; Zhonghua Liu (Food Chemistry, 2025)

Purification and identification of antioxidant activity and angiotensin converting enzyme (ACE) inhibitory activity peptide of peanut protein based on ultrafiltration (UF) membrane separation - Bin Cao; Qi Li; Zhenyu Chen; Xiuren Tang; Hock Eng Khoo; Tiemin Jiang; Yueming Jiang; Jing Li; Xinhong Dong (Food Bioscience, 2025)

Mapping of Rsn2, a locus conferring rice tolerance to toxin from the causal agent of rice sheath blight Rhizoctonia solani - Xiang Xue; Yu Wang; Yueming Xu; Yumei Zhang; Fang Gu; Yuyin Ma; Zongxiang Chen; Yafang Zhang (Journal of Plant Pathology, 2025)

Stability analysis on the positioning of steel caisson foundations during submerging stage under complex marine conditions - Minglin Chen; Yong Xiao; Yueming Jin; Yonggan Sun; Bo Huang (Ocean Engineering, 2025)

Molecular characterization of large yellow croaker (Larimichthys crocea) coagulation factor Ⅶ-like and its function on macrophage proliferation and polarization - Yueming Chen; Han Zhao; Shuangshuang Cao; Hongjun Xie; Jieyu Huang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2025)

Improving the functional components and biological activities of navel orange juice through fermentation with an autochthonous strain Lactiplantibacillus paraplantarum M23 - Meiling Huang; Chunling Lai; Yan Liang; Qin Xiong; Chaoyun Chen; Zhiran Ju; Yueming Jiang; Jun Zhang (Food and Bioproducts Processing, 2025)

Citrus exosome-modified exogenous dsRNA delivery reduces plant pathogen resistance and mycotoxin production - Chunxiao Yin; Yuli Lao; Lihong Xie; Lianfei Chen; Yueming Jiang; Liang Gong (Pesticide Biochemistry and Physiology, 2024)

A Tank Experiment of the Autonomous Detection of Seabed-Contacting Segments for Submarine Pipelaying Operations - Bo Wang; Jie Wang; Chen Zheng; Ye Li; Jian Cao; Yueming Li (Journal of Marine Science and Engineering, 2024)
Due to the weak structural features of pipelines and underwater light attenuation, the complex and harsh environment of the seabed greatly increases the possibility of an underwater autonomous remotely operated vehicle losing a detected seabed-contacting segment during pipe-laying operations. To address this problem, we propose a cascade attention module and a prefusion module with a convolutional neural network. The cascade attention module samples the feature maps in a non-convolutional form to realize the interaction between structure and channels, and the attention map is generated by cascading attention. The prefusion module pre-fuses the three layers of feature maps from different stages in the backbone, and the delicate features of the shallow feature maps are fused with the deeper feature maps to generate richer feature maps with space location and semantic classification information. We conduct experiments to verify our modules, both on the underwater pipeline dataset and in a tank test. The results show that our modules can improve the performance of different neural network models for seabed-contacting segment detection. The target detection and instance segmentation performance of the best model is improved through a 6.3% increase in AP and a 3.8% increase in mean intersection over union compared with the baseline model.

Multi-rater Prism: Learning self-calibrated medical image segmentation from multiple raters - Junde Wu; Huihui Fang; Jiayuan Zhu; Yu Zhang; Xiang Li; Yuanpei Liu; Huiying Liu; Yueming Jin; Weimin Huang; Qi Liu; Cen Chen; Yanfei Liu; et al. (Science Bulletin, 2024)

The effect of artificial intelligence evolving on hyperspectral imagery with different signal-to-noise ratio, spectral and spatial resolutions - Jianxin Jia; Xiaorou Zheng; Yueming Wang; Yuwei Chen; Mika Karjalainen; Shoubin Dong; Runuo Lu; Jianyu Wang; Juha Hyyppä (Remote Sensing of Environment, 2024)

The role of hydrogen-rich water in delaying the pulp breakdown of litchi fruit during postharvest storage - Huijun Gao; Feiyan Li; Xi Chen; Ziming You; Lei Wei; Yuanlong Liu; Ping Liu; Mingyang He; Min Hong; Hong Zhu; Xuewu Duan; Yueming Jiang; et al. (Food Chemistry, 2024)

Insight into the aroma and taste enrichment pattern in Chinese traditional braised soup based on HS-SPME-GC-MS and HS-GC-IMS - Feifei Wang; Debin Guo; Pingwei Wen; Haiqi Chen; Yueming Hu; Jun Li; Zongcai Tu; Hui Wang (Food Bioscience, 2024)

Lead exposure induces neurodysfunction through caspase-1-mediated neuronal pyroptosis - Dongjie Peng; Leilei Wang; Yuanyuan Fang; Lili Lu; Zhaocong Li; Siyang Jiang; Jing Chen; Michael Aschner; Shaojun Li; Yueming Jiang (Environmental Research, 2024)

A Method for Multi-AUV Cooperative Area Search in Unknown Environment Based on Reinforcement Learning - Yueming Li; Mingquan Ma; Jian Cao; Guobin Luo; Depeng Wang; Weiqiang Chen (Journal of Marine Science and Engineering, 2024)
As an emerging direction of multi-agent collaborative control technology, multiple autonomous underwater vehicle (multi-AUV) cooperative area search technology has played an important role in civilian fields such as marine resource exploration and development, marine rescue, and marine scientific expeditions, as well as in military fields such as mine countermeasures and military underwater reconnaissance. At present, as we continue to explore the ocean, the environment in which AUVs perform search tasks is mostly unknown, with many uncertainties such as obstacles, which places high demands on the autonomous decision-making capabilities of AUVs. Moreover, considering the limited detection capability of a single AUV in underwater environments, while the area searched by the AUV is constantly expanding, a single AUV cannot obtain global state information in real time and can only make behavioral decisions based on local observation information, which adversely affects the coordination between AUVs and the search efficiency of multi-AUV systems. Therefore, in order to face increasingly challenging search tasks, we adopt multi-agent reinforcement learning (MARL) to study the problem of multi-AUV cooperative area search from the perspective of improving autonomous decision-making capabilities and collaboration between AUVs. First, we modeled the search task as a decentralized partial observation Markov decision process (Dec-POMDP) and established a search information map. Each AUV updates the information map based on sonar detection information and information fusion between AUVs, and makes real-time decisions based on this to better address the problem of insufficient observation information caused by the weak perception ability of AUVs in underwater environments. Secondly, we established a multi-AUV cooperative area search system (MACASS), which employs a search strategy based on multi-agent reinforcement learning. The system combines various AUVs into a unified entity using a distributed control approach. During the execution of search tasks, each AUV can make action decisions based on sonar detection information and information exchange among AUVs in the system, utilizing the MARL-based search strategy. As a result, AUVs possess enhanced autonomy in decision-making, enabling them to better handle challenges such as limited detection capabilities and insufficient observational information.

Pore shrinkage capacity of Shajiang black soils (Vertisols) on the North China Plain and its influencing factors - Yueming CHEN; Zhongbin ZHANG; Lei GAO; Zichun GUO; Peng XIONG; Fahui JIANG; Xinhua PENG (Pedosphere, 2024)

Evaluating combustion kinetics and quantifying fuel-N conversion tendency of shoe manufacturing waste - Guang Sun; Lin Li; Yuanqiang Duan; Yuqing Chen; Quanbin Gu; Yueming Wang; Zhenkun Sun; Junhua Mao; Xiaodong Qian; Lunbo Duan (Environmental Research, 2024)

Improved hourly estimate of aerosol optical thickness over Asian land by fusing geostationary satellites Fengyun-4B and Himawari-9 - Yueming Cheng; Tie Dai; Daisuke Goto; Lin Chen; Yidan Si; Hiroshi Murakami; Mayumi Yoshida; Peng Zhang; Junji Cao; Teruyuki Nakajima; Guangyu Shi (Science of The Total Environment, 2024)

Structural insight into the dual-antagonistic mechanism of AB928 on adenosine A2 receptors - Yuan Weng; Xinyu Yang; Qiansen Zhang; Ying Chen; Yueming Xu; Chenyu Zhu; Qiong Xie; Yonghui Wang; Huaiyu Yang; Mingyao Liu; Weiqiang Lu; Gaojie Song (Science China Life Sciences, 2024)

The structure characteristics, biosynthesis and health benefits of naturally occurring rare flavonoids - Shengtao Bo; Sui Kiat Chang; Yipeng Chen; Zhili Sheng; Yueming Jiang; Bao Yang (Critical Reviews in Food Science and Nutrition, 2024)

Nitrogen-doped biochar/MnO2 as an efficient PMS activator for synergistic BPA degradation via non-free radical pathways in the water - Hang Chen; Xiao Li; Weizhuo Li; Jing Feng; Ying Zhao; Hexin Zhang; Yueming Ren (Journal of Environmental Chemical Engineering, 2024)

Vegetation recovery reshapes the composition and enhances the network connectivity of phoD-harboring microorganisms to promote P availability in a karst ecosystem - Fujing Pan; Xuan Yu; Min Chen; Yueming Liang (Science of The Total Environment, 2024)

Insight into the molecular mechanism underlying the enhancement of antioxidant activity in ovalbumin by high-energy electron beam irradiation - Haiqi Chen; Zhongyue Bian; Pingwei Wen; Hui Wang; Yueming Hu; Zongcai Tu; Guangxian Liu (Food Chemistry, 2024)

Hexaconazole and binary mixtures of it plus fludioxonil efficiently control tomato leaf mold caused by Cladosporium fulvum - Shuai Hu; Xiuhuan Li; Lele Chen; Yueming Wu; Lingtao Meng; Kai Wang; Beixing Li; Feng Liu (Crop Protection, 2023)

CD137L Inhibition Ameliorates Hippocampal Neuroinflammation and Behavioral Deficits in a Mouse Model of Sepsis-Associated Encephalopathy - Fang Qiu; Yueming Liu; Yang Liu; Zhuyun Zhao; Lile Zhou; Pengfei Chen; Yunbo Du; Yanmei Wang; Huimin Sun; Changchun Zeng; Xiaokang Wang; Yuqiang Liu; et al. (NeuroMolecular Medicine, 2023)
Anxiety manifestations and cognitive dysfunction are common sequelae in patients with sepsis-associated encephalopathy (SAE). Microglia-mediated inflammatory signaling is involved in anxiety, depression, and cognitive dysfunction during acute infection with bacterial lipopolysaccharide (LPS). However, the molecular mechanisms underlying microglia activation and behavioral and cognitive deficits in sepsis have not been in fully elucidated. Based on previous research, we speculated that the CD137 receptor/ligand system modulates microglia function during sepsis to mediate classical neurological SAE symptoms. A murine model of SAE was established by injecting male C57BL/6 mice with LPS, and cultured mouse BV2 microglia were used for in vitro assays. RT-qPCR, immunofluorescence staining, flow cytometry, and ELISA were used to assess microglial activation and the expression of CD137L and inflammation-related cytokines in the mouse hippocampus and in cultured BV2 cells. In addition, behavioral tests were conducted in assess cognitive performance and behavioral distress. Immunofluorescence and RT-qPCR analyses showed that hippocampal expression of CD137L was upregulated in activated microglia following LPS treatment. Pre-treatment with the CD137L neutralizing antibody TKS-1 significantly reduced CD137L levels, attenuated the expression of M1 polarization markers in microglia, and inhibited the production of TNF-α, IL-1β, and IL-6 in both LPS-treated mice and BV2 cells. Conversely, stimulation of CD137L signaling by recombinant CD137-Fc fusion protein activated the synthesis and release of pro-inflammatory cytokines in cultures BV2 microglia. Importantly, open field, elevated plus maze, and Y-maze spontaneous alternation test results indicated that TKS-1 administration alleviated anxiety-like behavior and spatial memory decline in mice with LPS-induced SAE. These findings suggest that CD137L upregulation in activated microglia critically contributes to neuroinflammation, anxiety-like behavior, and cognitive dysfunction in the mouse model of LPS-induced sepsis. Therefore, therapeutic modulation of the CD137L/CD137 signaling pathway may represent an effective way to minimize brain damage and prevent cognitive and emotional deficits associated with SAE.

Effects of different high-temperature conduction modes on the ovalbumin-glucose model: AGEs production and regulation of glycated ovalbumin on gut microbiota - Haiqi Chen; Yanru Zhou; Siqiong Zhang; Zuohua Xie; Pingwei Wen; Hui Wang; Yueming Hu; Peihan Wu; Jiaojiao Liu; Qiannan Jiang; Zongcai Tu (Food Research International, 2023)

Comparison of ovalbumin glycation induced by high-temperature steaming and high-temperature baking: A study combining conventional spectroscopy with high-resolution mass spectrometry - Yueming Hu; Haiqi Chen; Yifan Yang; Siqiong Zhang; Zuohua Xie; Jiaojiao Liu; Qiannan Jiang; Jun Liu; Pingwei Wen (Food Research International, 2023)

Interaction between ultrasound-modified pectin and icaritin - Yipeng Chen; Yueming Jiang; Lingrong Wen; Bao Yang (Food Chemistry, 2023)

In-situ measuring and predicting dynamics of soil bulk density in a non-rigid soil as affected by tillage practices: Effects of soil subsidence and shrinkage - Yuekai Wang; Zhongbin Zhang; Zichun Guo; Yueming Chen; Junsheng Yang; Xinhua Peng (Soil and Tillage Research, 2023)

Degradation of water-soluble polysaccharides in pulp of litchi during storage - Zhongsuzhi Chen; Meiying He; Yijie Zhou; Xi Chen; Hong Zhu; Bao Yang; Yueming Jiang; Hongxia Qu (Food Chemistry, 2023)

MiR-139-5p/ENAH Affects Progression of Hepatocellular Carcinoma Cells - Yueming Zhang; Meng Li; Yinghuan Qiu; Yuhua Wu; Shan Chen; Bin Ni; Ding Tang; Zhouzi Deng; Zhiqiang Hu (Biochemical Genetics, 2022)

DEM-CFD investigation on the effects of angularity and roughness on the mass loss of soil rock mixtures - Fan Chen; Yingchao Wang; Wen Jiang; Yin Guo; Yueming Wang (European Journal of Environmental and Civil Engineering, 2022)

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

Estimation of forest aboveground biomass by using mixed-effects model - Haoning Feng; Qi Chen; Yueming Hu; Zhiguo Du; Guantu Lin; Changwei Wang; Youju Huang (International Journal of Remote Sensing, 2021)

Safety and efficacy of new oral anticoagulants compared to those of warfarin in AF patients with cancer: a meta-analysis of randomized clinical trials and observational studies - Yueming Chen; Min Mao; Jing Chang; Jing Yan; Tiantian Yang; Yang Liu; Meng Luo; Yuhao Hu; Qi Yang; Lin Zhou; Kanghua Ma (European Journal of Clinical Pharmacology, 2021)

Effect of aluminate content in cement on the long-term sulfate resistance of cement stabilized sand - Kaiwei Liu; Yueming Wang; Ning-Jun Jiang; Aiguo Wang; Daosheng Sun; Xingxing Chen (Marine Georesources & Geotechnology, 2020)

Interaction between serine carboxypeptidase-like protein TtGS5 and Annexin D1 in developing seeds of Triticum timopheevi - Peihong Jiang; JianSheng Gao; Junyi Mu; Luning Duan; Yunsong Gu; Shichen Han; Lin Chen; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Aquaculture area extraction and vulnerability assessment in Sanduao based on richer convolutional features network model - Yueming Liu; Xiaomei Yang; Zhihua Wang; Chen Lu; Zhi Li; Fengshuo Yang (Journal of Oceanology and Limnology, 2019)

Object-based classification of cloudy coastal areas using medium-resolution optical and SAR images for vulnerability assessment of marine disaster - Fengshuo Yang; Xiaomei Yang; Zhihua Wang; Chen Lu; Zhi Li; Yueming Liu (Journal of Oceanology and Limnology, 2019)

Genome-wide identification of internal reference genes for normalization of gene expression values during endosperm development in wheat - Junyi Mu; Lin Chen; Yunsong Gu; Luning Duan; Shichen Han; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2019)

Phycocyanin fluorescent probe from Arthrospira platensis: preparation and application in LED-CCD fluorescence density strip qualitative detection system - Yunquan Zheng; Liuda Mo; Wenyi Zhang; Yunjian Duan; Jiandong Huang; Chengqun Chen; Yueming Gao; Xianai Shi; Feng Li; Jianmin Yang; Yanghao Guo (Journal of Applied Phycology, 2019)

Effect of vegetation types on soil arbuscular mycorrhizal fungi and nitrogen-fixing bacterial communities in a karst region - Yueming Liang; Fujing Pan; Xunyang He; Xiangbi Chen; Yirong Su (Environmental Science and Pollution Research, 2016)

Spatial variability of soil arsenic and its association with soil nitrogen in intensive farming systems - Yueming Hu; Zhenglei Jia; Jiachang Cheng; Zhizhong Zhao; Feixiang Chen (Journal of Soils and Sediments, 2016)

EOLA1 protects lipopolysaccharide induced IL-6 production and apoptosis by regulation of MT2A in human umbilical vein endothelial cells - Yueming Liu; Hairong Liu; Wenhai Chen; Ting Yang; Wei Zhang (Molecular and Cellular Biochemistry, 2014)

Diagnosing Climate Change and Hydrological Responses in the Past Decades for a Minimally-disturbed Headwater Basin in South China - Yiping Wu; Dongsheng Cheng; Wende Yan; Shuguang Liu; Wenhua Xiang; Ji Chen; Yueming Hu; Qian Wu (Water Resources Management, 2014)

Molecular characterisation and evolution of HMW glutenin subunit genes in Brachypodium distachyon L. - Saminathan Subburaj; Guanxing Chen; Caixia Han; Dongwen Lv; Xiaohui Li; Friedrich J. Zeller; Sai L. K. Hsam; Yueming Yan (Journal of Applied Genetics, 2014)

Natural Occurrence, Analysis, and Prevention of Mycotoxins in Fruits and their Processed Products - Jinyi Yang; Jing Li; Yueming Jiang; Xuewu Duan; Hongxia Qu; Bao Yang; Feng Chen; Dharini Sivakumar (Critical Reviews in Food Science and Nutrition, 2014)

Selection of surfactant in remediation of DDT-contaminated soil by comparison of surfactant effectiveness - Ping Guo; Weiwei Chen; Yueming Li; Tao Chen; Linhui Li; Guanzhu Wang (Environmental Science and Pollution Research, 2014)

Comparative analysis of basidiomycetous laccase genes in forest soils reveals differences at the cDNA and DNA levels - Xiangbi Chen; Yirong Su; Xunyang He; Yueming Liang; Jinshui Wu (Plant and Soil, 2013)

Removal of heavy metal ions from wastewater by a novel HEA/AMPS copolymer hydrogel: preparation, characterization, and mechanism - Zhengkui Li; Yueming Wang; Ningmei Wu; Qichun Chen; Kai Wu (Environmental Science and Pollution Research, 2013)

Paleogene-Neogene stratigraphic realm and sedimentary sequence of the Qinghai-Tibet Plateau and their response to uplift of the plateau - KeXin Zhang; GuoCan Wang; JunLiang Ji; ManSheng Luo; XiaoHu Kou; YueMing Wang; YaDong Xu; FenNing Chen; RuiMing Chen; BoWen Song; JianYu Zhang; YinPing Liang (Science China Earth Sciences, 2010)